STRUKTUR KEPEMILIKAN, PROFITABILITAS, PERTUMBUHAN AKTIVA DAN UKURAN PERUSAHAAN TERHADAP STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR - Kartini Kartini; Tulus Arianto (Jurnal Keuangan dan Perbankan, 2008)
This research aimed to test influence of the Ownership Structure, Profitability, Assetgrowth, and Size measure of firm to Capital Structure. This Research was limited onlymanufacturing company which had gone public in Jakarta Stock Exchange. This research wasconducted by taking secondary data. Population in this research was manufacturing companyobtained from share which was listed and go public in Jakarta Stock Exchange period 2002-2005. The intake technique was random sampling, and the obtained data was 38 companies.Result of analysis or T test in this research indicated that the ownership structure, asset growth,and size of company were significant or accepted. Only unprovable profitability was refused.While result F test showed that independent variable had an effect on the significance toCapital Structure of company in significance level 5%, and variable of size of company insignificance level 10%.